Genetic and epigenetic landscape of nasopharyngeal carcinoma - Dai, Wei; Zheng, Hong; Cheung, Arthur Kwok Leung; Lung, Maria Li (Chinese Clinical Oncology; Vol 5, No 2 (April 19, 2016): Chinese Clinical Oncology (Nasopharyngeal Carcinoma-Guest Editors: Joseph Wee, Yoke-Lim Soong, Melvin Chua), 2016)
Nasopharyngeal carcinoma (NPC) is a unique epithelial malignancy that shows a remarkable geographical and ethic distribution. Multiple factors including predisposing genetic factors, environmental carcinogens, and Epstein-Barr virus (EBV) infection contribute to the accumulation of genetic and epigenetic alterations leading to NPC development. Emerging technologies now allow us to detailedly characterize and understand cancer genomes. Genome-wide studies show that typically NPC tumors are characterized as having comparatively low mutation rates, widespread hypermethylation, and frequent copy number alterations and chromosome abnormalities. In this review, we provide an updated overview of the genetic and epigenetic aberrations that likely drive nasopharyngeal tumor development and progression. We integrate the previous knowledge and novel findings from whole-exome sequencing (WES) and methylome studies in NPC, and further discuss the potential use of these findings to identify biomarkers for NPC diagnosis and prognosis.